Morfologia e sedimentologia da plataforma continental interna do município de Acaraú - Ceará - Brasil - Moraes, M. V. A. R. (2015)
This paper shows the studies of the morphology and sedimentology of the Inner Continental Platform in the municipality of Acarau - Ceara. The method used in this work, was initially performed bibliographic and cartographic research, field survey (sample collection) and granulometric analyzes. According to the results obtained for the continental shelf, the bathymetric model showed a morphology of homogeneous background from isobath 0 to 12m. As from the isobath 12m, the relief presented with low declivity and with few irregularities such as rolling hills and tidal channels. The result of the granulometric analysis showed the continental shelf with predominantly bioclastic sand, characterized for present 70% to 100% sand, and from 70% to 100% of CaCO3, so represented a gritty continental shelf.